Cosmetic Products with Halal Labels to Generation Z Does it Matter? - Eti Kusmiati (El-Qish: Journal of Islamic Economics, 2023)
The demand for halal products in Indonesia is increasing and expanding. Not only for food products but has expanded to other product categories such as cosmetics, pharmaceuticals, financial services, and tourism. Indonesia is one of the cosmetic markets that are quite large so the business is prospective and promising. The potential of this domestic market includes the increasing number of young population or generation Z. This study aims to further analyze the factors that drive the behavior of consumers of generation Z towards purchasing decisions of halal cosmetic products. This study uses a qualitative approach with a descriptive survey technique. The analysis was carried out on primary data obtained from interviews with informants. From the predetermined criteria, 15 women were obtained as informants. Findings. The results of the study found that the consumption pattern of cosmetics in Generation Z was driven by product quality, price, halal labels, and brand ambassadors. Further findings state that although generation Z knows and believes in the truth in religion, these beliefs and knowledge are not internalized in consuming halal cosmetics.